Diagnosis and management of fungal endophthalmitis: India perspective. (1st November 2020) - Das, Taraprasad; Agarwal, Manisha; Behera, Umesh; Bhattacharjee, Harsha; Bhende, Muna; Das, Anthony V.; Dave, Vivek P.; Dogra, Avantika; Ghosh, Anup K.; Giridhar, Sneha; Joseph, Joveeta; Kandle, Kaustubh; et al.
ABSTRACT: Introduction: Fungal Endophthalmitis is a potentially blinding condition, and difficult to treat. It is more often reported from Asia, including India. The mainstays of treatment are vitrectomy and intravitreal injection of antifungal agents. Areas Covered: The current clinical and microbiological diagnoses of fungal endophthalmitis, both exogenous and endogenous, are discussed. The mechanisms of action and delivery routes of antifungal agents are discussed. The characteristics of endophthalmitis caused by three common species, Aspergillus, Candida, and Fusarium are described. Published data from 2009 to 2019 from India and additional data collected from 7 large referral centers spread across India are presented. Expert Opinion: Published data suggest a clear benefit from vitrectomy and intravitreal antifungals agents in fungal endophthalmitis though it is likely that many eyes are initially treated with intravitreal bacterial antibiotic only. This is probably related to lack of unequivocal clinical differentiation. Possibly not much harm is inflicted if the specific treatment is instituted as soon as laboratory evidence is available. The future research should focus on early clinical and laboratory diagnosis. Big data analysis to identify the clinical biomarkers and newer laboratory technology to early detection of fungal infection should improve management of this condition that has a poor prognosis.